Green Extraction Methods for Recovery of Antioxidant Compounds from Epicarp, Seed, and Seed Tegument of Avocado var. Hass (Persea americana Mill.) - Juan F. Grisales-Mejía; Harlen Torres-Castañeda; Margarita M. Andrade-Mahecha; Hugo A. Martínez-Correa (International Journal of Food Science)
The present study compared the extracts obtained from the epicarp, seed, and seed tegument of avocado var. Hass with pressurized liquid extraction (PLE) and ultrasound-assisted extraction (UAE). The extracts were quantified in terms of total phenolic content (TPC) and antioxidant capacity (AC). The PLE extracts had a global yield (X0) like that obtained with UAE using ethanol (Et) as the solvent. For the TPC, the extracts obtained with both techniques showed no significant differences (p>0.05). On the other hand, the epicarp extracts obtained with PLE had higher values for AC: 829.8 μmol TE/gDe (ABTS) and 3,215.1 μmol Fe2+/g De (FRAP), recorded for UAE/Et. The AC in the avocado residue extracted with PLE suggested a high potential for applications in food, pharmaceutical, and cosmetology products.